Assessment of circadian rhythm in pain and stiffness in rheumatic diseases according the EMA (Ecologic Momentary Assessment) method: patient compliance with an electronic diary - R. Procaccini; A. Stancati; F. Salaffi; F. Cioni; W. Grassi (PAGEPress Publications, 2011)
Background: Many researchers have used paper diaries in an attempt to capture patient experience. However, patient non-compliance with written diary protocols is a serious problem for researchers. Electronic patient experience diaries (eDiary) facilitate Ecologic Momentary Assessment (EMA) study designs by allowing the researcher to administer flexible, programmable assessments and mark each record with a time and date stamp. Objectives: The objectives of the current study were to evaluate methodological issues associated with real-time pain reports (EMA) using electronic patient experience diaries, to quantify compliance (percentage of the total number of diary reports scheduled that were actually completed), and to examine the circadian rhythm in pain and stiffness of patients with rheumatic diseases in an ecologically valid manner. Methods: In this cross-sectional study we examined 49 patients with rheumatic diseases (14 patients with rheumatoid arthritis, 18 with fibromyalgia and 17 with osteoarthritis of the knee), attending the care facilities of the Department of Rheumatology of Università Politecnica delle Marche. All patients fulfilling the American College of Rheumatology (ACR) criteria. The assessment of pain and stiffness in all patients were repeated seven times a day (8 A.M., 10 A.M., 12 A.M., 2 P.M., 4 P.M., 6 P.M. and 8 P.M.) on seven consecutive days using an electronic diary (DataLoggerÒ - Pain Level Recorder). A datalogger is newly developed electronic instrument that records measurements of pain and stiffness over time. Dataloggers are small, battery-powered devices that are equipped with a microprocessor. Specific software is then used to select logging parameters (sampling intervals, start time, etc.) and view/analyse the collected data. Compliance is based on the time and date record that was automatically recorded by the devices. Results: Using the data from the electronic diary, we determined that the average verified compliance rate for pain and stiffness were 93.8 and 93.6%, respectively. The two highest compliance rates were observed in patients with rheumatoid arthritis (95.6 and 95.2%, respectively). There were no statistically significant difference in compliance between females and males or patients above or below 60 years old. Significant circadian rhytms in patients with RA and OA of the knee were detected in pain and stiffness. No rhythm in pain or stiffness was observed in subjects with fibromyalgia. Conclusions: We conclude that collection of subjective data using electronic diary in rheumatologic setting is a feasible method than can be adopted with high compliance rates across a range of patient demographic subgroups. The identification of diurnal cycles of self-reported pain and stiffness, using EMA method, has important implications for patients with respect to planning their daily activities and in developing individual therapeutic programs with respect to diurnal variability, which therefore may be more effective.